Preparation of pooled blood samples to use as a proficiency Testing material for hemoglobin a1ctesting byturbidimetric Inhibition immunoassay - P.WONGSRI,; K.KONGROS,; P.SAKAEW,; W.TREEBUPHACHATSAKUL, (International Journal of Pharma and Bio Sciences, 2018)
Hemoglobin A1c (HbA1c) or glycated hemoglobin testing is used to monitor the degree of glucose metabolism in diabetic patients. This study aims to evaluate pooled whole blood samples are available proficiency testing materials (PT materials) for HbA1c testing by turbidimetric inhibition immunoassay(Indiko™).The constituent whole blood samples, taken from 30 diabetic patients, were left over from routine laboratory work.The specimens were divided into two groups, Group 1 (n=15) diabetic patient specimens with normal hemoglobin, and Group 2 (n=15) diabetic patient specimens with low hemoglobin (Hb<12 g/dl).From each group, the samples had different HbA1c levels, 4.0 - 6.4, 6.5 – 9.9 and 10.0 – 14.0%, each level had pooled of five original samples. After that, the samples were washed and suspended in citrate phosphate dextrose adenine 1 (CPDA1). Then,samples were randomly selected for homogeneity and stability testing at stored 2-6 0C and -20 0C, in accordance with ISO 13528: 2015 Annex B.Coefficient of variation (CV) of within a run and between a run of HbA1c were range from 1.48% to 1.73% for quality control level 1 and 2.Blood materials prepared from both groups of Hb were homogeneous and could stable for at least 15 days at 2-6 0C and -20 0C.Blood materials from pooled whole blood sample suspended in CPDA1 solution were stable at least two weeks at 2-6 0C and -20 0C by turbidimetric inhibition immunoassay and also avoidobtainable volume from diabetic patients.Moreover, further studies are required to estimate of PT material on multiple assays.